2010
DOI: 10.1021/ja909578s
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ce3+ Codoping and Annealing on Phase Transformation and Luminescence of Eu3+-Doped YPO4 Nanorods: D2O Solvent Effect

Abstract: Ce(3+)- and Eu(3+)-doped YPO(4) nanorods have been prepared at relatively low temperature (120 degrees C). A detailed investigation of the role of Ce(3+) concentration up to 10 atom % on the luminescence intensity of Eu(3+) in Ce(3+)- and Eu(3+)-doped YPO(4) has been carried out. Phase transformation from a tetragonal to a hexagonal structure occurs with increasing Ce(3+) concentrations, and water molecules are also associated during phase transformation. Thermal study shows that water can be retained up to 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
133
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(137 citation statements)
references
References 39 publications
3
133
1
Order By: Relevance
“…4(c)), we observe a small peak at ∼141.1 eV which corresponds to Eu 3+ (4d 3/2 ) and no peak corresponding to Eu 2+ (4d 5/2 ) is observed at ∼127.1 eV. 24 This confirms the high probability of Eu 3+ present in samples. Figure 4(d) shows the XPS spectra of Y(2p 1/2 ) and its corresponding peaks at ∼299.4, 300.1 eV for 0 and 10 at.% Li + YPO 4 :5Eu samples are observed.…”
Section: Xps Studysupporting
confidence: 77%
See 1 more Smart Citation
“…4(c)), we observe a small peak at ∼141.1 eV which corresponds to Eu 3+ (4d 3/2 ) and no peak corresponding to Eu 2+ (4d 5/2 ) is observed at ∼127.1 eV. 24 This confirms the high probability of Eu 3+ present in samples. Figure 4(d) shows the XPS spectra of Y(2p 1/2 ) and its corresponding peaks at ∼299.4, 300.1 eV for 0 and 10 at.% Li + YPO 4 :5Eu samples are observed.…”
Section: Xps Studysupporting
confidence: 77%
“…22 It was reported that Y-O bond length changes whereas P-O bond length almost remains the same on annealing YPO 4 nanoparticles at higher temperatures. 23 In past few years, Ningthoujam and his co-workers 24 has examined the luminescence properties of Ln 3+ ion doped YPO 4 nanoparticles. It was found that the presence of water molecules up to 800 • C in Ce 3+ co-doped YPO 4 :Eu was observed and thus the luminescence intensity was quenched significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Due to a sharp emission, these compounds are also used as host for luminescence applications 6,7,13 including lasers and display devices. A combination of rare-earth phosphates and silicates is used as host for nuclear wastes 14 .…”
Section: Introductionmentioning
confidence: 99%
“…LaPO4 crystallizes in two polymorphs, namely, the tetragonal phase (xenotime structure) and the monoclinic phase (monazite structure). Yttrium orthophosphate, YPO4, also has the tetragonal symmetry (xenotime type) 6 . Doping YPO4 matrix with Ce 3+ and Eu…”
mentioning
confidence: 99%
See 1 more Smart Citation